Pertanggungjawaban Hukum Bagi Pelaku Usaha Atas Praktek Monopoli dan Persaingan Usaha Tidak Sehat dalam Pembangunan Rumah Sakit - Panjaitan, Lola; Maswandi, Maswandi; Rafiqi, Rafiqi (Universitas Medan Area, 2023)
This study aims to determine the regulation of liability for business actors who commit monopolistic practices and unfair business competition in hospital construction based on KPPU Decision Number 04/KPPU-L/2020 and the legal consequences of monopolistic practices and unfair business competition in the Langsa Region of Aceh Province. Normative legal research method, with a statutory approach. The research concluded that the provisions regarding the legal liability of business entities have two types of sanctions, namely administrative sanctions and criminal sanctions. In this case, it is proven that the Reported Party I and Reported Party VII violated Law No. 5 of 1999. so that the Reported Party I is subject to administrative sanctions in the form of a fine of RP 1,723,500,000.00 and the legal consequences of this decision are the Business Competition Supervisory Commission imposing administrative sanctions on the Reported Party I PT Mina Fajar Abadi.